Finding Effective Compiler Optimization Sequences: A Hybrid Approach - Queiroz Junior, Nilton Luiz; da Silva, Anderson Faustino; Rodriguez, Luis Gustavo Araujo (Computing and Informatics, 2021)
The Optimization Selection Problem is widely known in computer science for its complexity and importance. Several approaches based on machine learning and iterative compilation have been proposed to mitigate this problem. Although these approaches provide several advantages, they have disadvantages that can hinder the performance. This paper proposes a hybrid approach that combines the best of machine learning and iterative compilation. Several experiments were performed using different strategies, metrics and hardware platforms. A thorough analysis of the results reveals that the hybrid approach is a considerable improvement over machine learning and iterative compilation. In addition, the hybrid approach outperforms the best compiler optimization level of LLVM.